2017
DOI: 10.1021/jacs.7b06401
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Localized and Free Charge Carriers Can Explain Hot Fluorescence in the CH3NH3PbBr3 Perovskite: Time-Domain Ab Initio Analysis

Abstract: Delayed high-energy fluorescence observed experimentally in methylammonium lead bromine CHNHPbBr (MAPbBr) demonstrates long-lived energetic charge carriers with extremely high mobilities that can be used to enhance photon-to-electron conversion efficiency of perovskite solar cells. It has been suggested that hot fluorescence is associated with reorientational motions of the MA molecules. We support this hypothesis by time-domain ab initio quantum dynamics calculations showing that reorientation of the MA molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 79 publications
4
86
0
Order By: Relevance
“…This carrier localization and self-trapping into large polarons occurred preferentially at elevated temperatures due to the strongly anharmonic potential of the halide perovskite lattice. Fortunately, the formation of large polarons enhanced the charge recombination lifetime by nearly an order of magnitude through a combination of a small reduction in mobility, 16,36,37 reduction of wavefunction overlap, 66 and introduction of energetic barriers to electron-hole recombination. 67 Our findings reveal the influence that atomic-scale fluctuations can have on the interplay between carrier transport and recombination in halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…This carrier localization and self-trapping into large polarons occurred preferentially at elevated temperatures due to the strongly anharmonic potential of the halide perovskite lattice. Fortunately, the formation of large polarons enhanced the charge recombination lifetime by nearly an order of magnitude through a combination of a small reduction in mobility, 16,36,37 reduction of wavefunction overlap, 66 and introduction of energetic barriers to electron-hole recombination. 67 Our findings reveal the influence that atomic-scale fluctuations can have on the interplay between carrier transport and recombination in halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the unique structure of 2D OIHPs, involving polar organic molecules with many degrees of freedom embedded within a rather rigid inorganic Pb-I framework, motions of the organic component can greatly affect the perovskite photovoltaic properties such as conductivity and mobility 53 . For instance, rotation and other rearrangement of the highly anisotropic and polar organic molecules can “solvate” the charge carriers, and thus screen the interaction of charge carriers with longitudinal optical (LO) phonons, which is accompanied by deformation of the inorganic framework 54 , 55 . Unfortunately, molecular structures of [PbI 6 ] 4− -bound organic molecules are not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…106 Zhang et al supported the proposition of the reorientational motion of MA molecules to lead to the pronounced hot fluorescence in MAPbBr 3 . 107 In a recently published time domain ab initio study they showed that depending on the MA orientation, low energy structures give rise to polaron-like electrons and holes, whilst the higher energy structures lead to more delocalised wavefunctions -interpreted as free carriers. They hence propose a two-emitter system of the MAPbBr 3 perovskite with hot and regular luminescence components.…”
Section: Perovskitesmentioning
confidence: 99%